Dynamics of ASEAN as Regional Organization in Resolving Human Security Issues in Southeast Asia - Hakim, Siti; Yusnaldi; Uksan, Arifuddin; Setiawibawa, Rachmat (International Journal of Education, Vocational and Social Science, 2026)
This study examines the dynamics of ASEAN as a regional organization in the context of the shifting security paradigm from traditional state-centric security to non-traditional human security, with a specific focus on natural disaster management. Southeast Asia is highly vulnerable to massive, cross-border natural disasters that often overwhelm national capacities. However, the prevailing "ASEAN Way," which emphasizes the principles of absolute state sovereignty and non-intervention, creates significant obstacles to effective humanitarian response, particularly when member states are unable or unwilling to accept aid due to internal conflict or lack of capacity. Using normative legal research methods based on secondary legal materials, this article argues that the principle of state sovereignty must be reinterpreted as a responsibility to protect human rights rather than a barrier to international aid. The study concludes that to resolve human security issues effectively, ASEAN must strengthen the principle of international cooperation and ASEAN centrality. This includes empowering the ASEAN Coordinating Centre for Humanitarian Assistance (AHA Centre) and the ASEAN Secretary-General to play a more active, independent role in decision-making during humanitarian emergencies.